2016
DOI: 10.1175/jcli-d-15-0727.1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Attribution of Recent Variability in Atlantic Overturning

Abstract: Attributing observed variability of the Atlantic meridional overturning circulation (AMOC) to past changes in surface forcing is challenging but essential for detecting any influence of anthropogenic forcing and reducing uncertainty in future climate predictions. Here, quantitative estimates of separate contributions from wind and buoyancy forcing to AMOC variations at 25°N are obtained. These estimates are achieved by projecting observed atmospheric anomalies onto model-based dynamical patterns of AMOC sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
97
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 58 publications
(110 citation statements)
references
References 69 publications
12
97
1
Order By: Relevance
“…The computations use the tangent linear and adjoint versions of the NEMO ocean model 20 in its ORCA2 configuration (2 • ×2 • horizontal resolution and 31 vertical levels). Although this configuration is relatively coarse, the general approach represents state-of-the-art in adjoint ocean modeling 16,18,19 . In addition, this resolution allows filtering out baroclinic instability that would contaminate the solutions otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…The computations use the tangent linear and adjoint versions of the NEMO ocean model 20 in its ORCA2 configuration (2 • ×2 • horizontal resolution and 31 vertical levels). Although this configuration is relatively coarse, the general approach represents state-of-the-art in adjoint ocean modeling 16,18,19 . In addition, this resolution allows filtering out baroclinic instability that would contaminate the solutions otherwise.…”
Section: Discussionmentioning
confidence: 99%
“…This quantification is most efficiently accomplished using an adjoint modeling approach that provides the linear sensitivity of the AMOC at a single latitude to changes in surface forcing over the globe, for all forcing lead times (Pillar et al 2016). Sensitivity glider sampled a strong anticyclonic eddy between the M3 and M4 moorings (Fig.…”
Section: Hydrography Across the Irminger And Labrador Seasmentioning
confidence: 99%
“…In particular, a break point in coherence may occur at the subpolar-subtropical gyre boundary in the North Atlantic (Bingham et al 2007;Baehr et al 2009). Furthermore, a recent modeling study has suggested that the low-frequency variability of the RAPID-MOCHA appears to be an integrated response to buoyancy forcing over the subpolar gyre (Pillar et al 2016). Thus, a measure of the overturning in the subpolar basin contemporaneous with a measure of the buoyancy forcing in that basin likely offers the best possibility of understanding the mechanisms that underpin AMOC variability.…”
mentioning
confidence: 99%
“…Given limited resources, the ASTE adjoint sensitivity tool (e.g., Heimbach et al, 2011;Pillar et al, 2016) can be used to identify optimal sites for float deployments in data-deficient regions such as the eastern Arctic as follows. First, a target quantity of interest (QoI), such as the mean salinity of Box B within a depth range covering the AW layer (145-250 m, green box in Figure 2c), is defined.…”
Section: The Need For Additional Alps Data For Observing-network Designmentioning
confidence: 99%